Metagenomic analysis provides bases on individualized shift of colon microbiome affected by delaying colostrum feeding in neonatal calves - Song, Yang; Wen, Shubo; Li, Fuyong; Fischer-Tlustos, Amanda; He, Zhixiong; Guan, Le Luo; Steele, Michael (Frontiers in Microbiology, 2022)
This study investigated the effect of colostrum feeding time on the colon digesta microbiome of 2-d old dairy calves using whole-genome sequencing technology, aiming to understand the dynamic changes of the colon microbiome with respect to delayed colostrum feeding. In total, 24 male Holstein calves were grouped to different colostrum feeding time treatments randomly: TRT0h (45 min after birth, n = 7); TRT6h (6 h after birth, n = 8); and TRT12h (12 h after birth, n = 9). Bacteria, archaea, eukaryotes, and viruses were identified in the colon microbiome, with bacteria (99.20%) being the most predominant domain. Streptococcus, Clostridium, Lactobacillus, Ruminococcus and Enterococcus were the top five bacteria at genus level. For colon microbiome functions, 114 Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways were identified, with nutrients metabolism related functions “carbohydrate metabolism”, “amino acid metabolism”, “metabolism of cofactors and vitamins”, “metabolism of terpenoids and polyketides”, and “metabolism of other amino acids” being the top five secondary level of KEGG hierarchy functions. When colon microbiomes were compared among the three colostrum feeding treatments, the overall colon microbiome was not affected by delaying first colostrum feeding through PERMANOVA analysis at both taxonomic and functional levels. However, two distinct clusters of colon microbiome profiles were detected in spite of different colostrum feeding treatment. Meanwhile, significant correlation relationships were observed between differentially expressed genes, microbial taxa and microbial functions of the two distinct clusters. Our results suggest that the host may play an important role in shaping the colon microbiome of neonatal dairy calves, which indicates that individual animal variation may be linked to calf gut health. However, whether colon microbiome shifts affect gut function in the long term is unknown and requires further research.